Assessing the learning outcomes of 8th-grade students from the National Exam in 2023 in Dire Dawa, Ethiopia - Goshu, Belay Sitotaw; Abas, Ermias; Fitria, Fitria (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2024)
The purpose of the study is to assess and examine the learning objectives attained by eighth-grade students who took part in the 2023 National Exam in Dire Dawa, Ethiopia. The study's descriptive research design gathers data on academic performance in the eighth grade. Every primary school, both private and public, was selected. Data was gathered from the education bureau using the academic roster for the 2023 national test. The descriptive approach was used to evaluate the student's progress toward the next level and their academic accomplishment. Using Python 3.11 software, the assessment was completed by classifying the students based on their mother tongue. The findings of the study indicated that in the Afan Somali stream, the average grade points for pupils in the academic year 2023 were 28.2 , 22.3 21.2 , 16.7 , 20.5 , and, 20.0 , respectively, in the fields of the Afan Somali language, English, citizenship, mathematics, social studies, and general science.  The average grade points for students in the Afan Oromo stream in the academic year 2023 were 28.4 , 20.3 20.4 , 17.1 , 22.6 , and 21.0 , respectively, in the fields of the Afan Somali language, English, citizenship, mathematics, social studies, and general science. Moreover, in Amharic, the average grade points for pupils in the academic year 2023 were 33.2 , 22.6 19.9 , 18.5 , 22.6 , and, 21.2 , respectively, in the fields of Amharic, English, citizenship, mathematics, social studies, and general science. According to these results, 26.4% of students who received scores higher than 50% and 73.6% of students who received scores lower than 50% were advanced to the next grade. However, the study suggests that primary schools should be equipped with the tools required to support high academic achievement. It is imperative to look for teachers who possess the necessary training, experience, aptitude for learning, and teaching abilities. According to their mother tongue languages, kids' academic performance varies, as evidenced by the results, which highlights the need for customized teaching strategies. The recommendations of the study for areas that warrant more investigation, such as studies on instructional materials and teacher quality carried out in elementary schools to get complete comparisons and identify other factors influencing learning results.